Conversas sobre a formação em psicologia e o trabalho para o Sistema Único De Saúde - Santos, Renata Guerda de Araújo (2013)
Training in Psychology in Brazil, produces a design different from that advocated by the ethical guidelines and policies of the Unified Health System (SUS). Guided by the guidelines of SUS in the training of psychologists have produced effects in the curriculum and in the Proposals Political-Pedagogical courses. In this orientation, some devices have been built problematizing new proposals from the Integration Service-Learning. Thus, we locate our research in the micropolitics of these processes in order to discuss the formation in Psychology from the introduction of policies and practices for the SUS. We take the guesswork of Social Research and Practice and Discursive Production of Meaning in Everyday Life as guiding frameworks, working from a cartographic composition in building a look from near and inside, moving this way, some of the regularities of science. Inspired by the movement of live Ethnomethodology, we present our presence in the field-theme exploring the various possibilities in everyday conversations. Conversations conducted two wheels, guided by triggering questions related to themes of research. These wheels were considered privileged methodological and informal spaces, ensuring the flow of conversation. The analysis was performed from the encounter with literature, the text of Italo Calvino "The six proposals for the next millennium," the dialogues with texts and discussions on training in Psychology and SUS during the search. Preserving the lessons of Calvin (lightness, quickness, exactitude, visibility and multiplicity and consistency) for training in Psychology is a guide that allowed us to discuss the core issues for research: a) How to think training in Psychology adopting the integration of teaching and community service-like enhancer element and converging with the Brazilian Public Health Policy? b) How does training in psychology has produced subject to job oriented / tuned for SUS? We conclude that the formation of labor for SUS happens in life, and the life of cities and people need to take concrete spaces in existing devices trainers for SUS.